The effect of glycerol and desmopressin on exercise performance and hydration in triathletes - Inder, W. J.; Swanney, M. P.; Donald, R. A.; Prickett, T. C.; Hellemans, J. (Medicine & Science in Sports & Exercise, 1998)
his study examined the effect of glycerol and the AVP analog desmopressin (DDAVP) on hydration and exercise performance in triathletes ingesting routine volumes of prerace fluids. Result: Although maintaining adequate hydration remains important for the endurance athlete, the routine use of either glycerol or DDAVP before athletic training or competition in a thermoneutral environment does not seem to confer any advantage over conventional fluid replacement.